2010
DOI: 10.1038/pcan.2010.40
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer at the peripheral end of a prostate biopsy specimen as assessed by a novel marking technique may indicate increased risk of locally advanced disease

Abstract: The objective of this study was to test a novel technique of processing a prostate biopsy (PB) specimen by marking its peripheral end (PE) as a predictive tool for locally advanced prostate cancer (PC) or margin-positive resection (R1) after radical prostatectomy (RP). Prospective evaluation of a consecutive cohort of men who underwent PB and subsequent RP was carried out. Transrectal ultrasound-guided 10-20 core PB was performed according to a standardized protocol. Each biopsy core was inked at the PE and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This pathological feature could have potential clinical advantage in the surgical management. Ponholzer et al showed that men, with at least one core with cancer at the inked peripheral margin, had a 3.1-fold (95% CI: 1.1–9.9) increased risk for locally advanced tumour stage in the final surgical specimen [7]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This pathological feature could have potential clinical advantage in the surgical management. Ponholzer et al showed that men, with at least one core with cancer at the inked peripheral margin, had a 3.1-fold (95% CI: 1.1–9.9) increased risk for locally advanced tumour stage in the final surgical specimen [7]. …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the clinical information provided by individually labelled (cancer site itself) was previously stated not useful and not convenient to justify the increased associated costs [18]. Surprisingly, when Ponholzer et al [7] considered the cancer location within the core (cancer located at the peripheral end of the specimen), they showed a significant correlation to pT3/pT4 stage ( P = 0.04) in multivariate analyses of 100 cases. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation